Sexual risk behaviour among Malaysian youth – a nationwide cross-sectional study - Mohamad, Fadzilah; Mohd Azlan, Syifa’; Kamaruddin, Khairatul Nainey; Shibraumalisi, Nuramirah; Syed Mohamad, Sharifah Najwa; Dahlan, Rahima; Ismail, Irmi Zarina; Shamsuddin, Nurainul Hana; Shahar, Kadir (Malaysian Family Physician, 2024)
Youths are typically at their peak of exploring new things including sexual risk behaviour (SRB) which often results in multiple reproductive health problems, complications and death. This study aims to determine the prevalence and association between multi-system factors and SRB among local youths studying in higher education institutions.